The Validity of Notarial Deeds Using Electronic Signatures - Teges Ayu Pranihita; Putu Ayu Sriasih Wesna; Ida Bagus Agung Putra Santika (Journal of Social Research, 2026)
This study examines the legal validity of electronically signed supporting documents (warkah) in notarial deeds within the framework of Indonesian notarial and cyber law. The rapid development of information technology and the increasing use of electronic signatures in legal transactions have created legal uncertainty due to the lack of synchronization between the Notary Office Law (UUJN-P) and the Information and Electronic Transactions Law (UU ITE). The research aims to analyze the validity of electronically signed warkah in notarial practice and to formulate future regulatory frameworks to support the implementation of cyber notary services in Indonesia. This study employed a mixed-method approach combining normative juridical analysis and empirical legal research. Normative analysis was conducted through the examination of legislation, legal doctrines, and legal theories, while empirical data were collected through interviews, observations, and documentation involving practicing notaries in Badung Regency. The findings reveal that electronically signed warkah have not yet obtained full legal recognition under the current UUJN-P because notarial protocols still require the physical binding of documents. This condition creates a legal antinomy between conventional notarial regulations and electronic transaction laws, potentially weakening the evidentiary value of authentic deeds and degrading them into private deeds. The study concludes that legal harmonization between the UUJN-P, UU ITE, Archives Law, and Stamp Duty Law is urgently required to establish a secure and legally certain cyber notary framework. Future regulations should recognize certified electronic signatures and electronic protocols as integral components of modern notarial services.